Partial cross ownership and explicit collusion - Johannes Paha; Samuel de Haas (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This article studies the unilateral and coordinated effects of non-controlling minority shareholdings (NCMS). It provides a comprehensive model by integrating the established models of Reynolds and Snapp (1986), Flath (1991), Malueg (1992), and Gilo et al. (2006). It is the first to add a competition authority. The model finds that NCMS lower the sustainability of collusion under a greater variety of situations than was indicated by earlier literature. The collusion destabilizing effect of NCMS is particularly prevalent in the presence of an effective antitrust authority.
Keywords: G34; K21; L41; 330